1963
DOI: 10.1126/science.139.3559.1063
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Concentration Quenching of Morphine Fluorescence

Abstract: Fundamental fluorescence equations were examined. Deviations from the theoretical were observed by varying the light path length to determine effects on "apparent" fluorescence. It was found that the decrease in emission of morphine solutions with the increase in concentration was caused by absorption effects that prevented excitation of the whole system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1963
1963
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…One well-known problem in fluorescence measurements is, however, the fluorescence inner filter effect (IFE) that can cause fluorescence spectral distortion and nonlinearity between fluorescence signal intensity and fluorophore concentration. Fluorescence IFE occurs whenever there are photon absorbers and scatterers in the sample solution, and it is in effect even without exogenous molecular or nanoparticle-based light absorbers or scatterers. This is because fluorophores must absorb excitation photons in order to emit.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One well-known problem in fluorescence measurements is, however, the fluorescence inner filter effect (IFE) that can cause fluorescence spectral distortion and nonlinearity between fluorescence signal intensity and fluorophore concentration. Fluorescence IFE occurs whenever there are photon absorbers and scatterers in the sample solution, and it is in effect even without exogenous molecular or nanoparticle-based light absorbers or scatterers. This is because fluorophores must absorb excitation photons in order to emit.…”
mentioning
confidence: 99%
“…It has been long realized that the degree of the fluorescence IFE is related to the sample UV–vis intensities at the excitation and emission wavelengths and the effective excitation and emission path lengths of the fluorophotometers. , ,, While UV–vis intensities of the samples can be extracted straightforwardly from the sample UV–vis spectrum, determination of the effective excitation and emission path lengths of a fluorophotometer is a nontrivial task . Figure shows a typical instrument configuration of a fluorophotometer in which the emitted photons are collected with a 90 deg angle relative to the excitation beam.…”
mentioning
confidence: 99%
“…However, it should be noted that the fluorescence intensity seemed to increase with the complex formation, suggesting that a certain fluorescence quenching in free form might affect the polarization (both the polarization intensity and the polarization potency). A previous study showed the fluorescence quenching may be influenced by factors such as solvent, van der Waals force, 26 concentration, 27 etc. It means the I ∥ − I ⊥ index is affected by not only fluorescence polarization but also fluorescence intensities, some of which may be caused by fluorescence quenching.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Besides the collective NP surface effect, NPs also modify fluorophore fluorescence through the fluorescence inner filter effect (IFE). IFE is well-known in fluorescence and Raman spectroscopy and is attributed to the attenuation of excitation and emission light intensities induced by photon absorbers and scatterers in the sample solution. ,,, Critically, fluorescence IFE is in play for all fluorophores in the NP-containing solution regardless of whether or not the fluorophore is adsorbed onto NPs. In addition, all NPs can impose strong IFE on fluorophore fluorescence.…”
Section: Introductionmentioning
confidence: 99%